Retinoic Acid Alleviates Cisplatin-Induced Acute Kidney Injury Through Activation of Autophagy - Wu, Junxia; Zheng, Canbin; Wan, Xin; Shi, Mingjun; McMillan, Kathryn; Maique, Jenny; Cao, Changchun (Frontiers in Pharmacology, 2020)
Cisplatin-induced acute kidney injury (CIAKI) is a common complication in patients receiving cisplatin-based chemotherapy. But the effective therapies for CIAKI are not available. Retinoic acid (RA), the main derivative of vitamin A, has the potential to reduce inflammation and fibrosis in renal injury. However, the effect and mechanism of RA on CIAKI is still unclear. The aim of this study is to investigate whether RA can alleviate CIAKI through activation of autophagy. In this study, we evaluated the effect of RA, RA’s effect on autophagy and apoptosis after cisplatin-induced injury on renal tubular epithelial cells (RTECs) by LDH assay, immunoblotting and TUNEL staining. Then we established Atg5flox/flox:Cagg-Cre mice in which Cagg-Cre is tamoxifen inducible and Atg5 is conditional deleted after tamoxifen injection. The effect of RA and RA’s effect on autophagy on CIAKI model was evaluated by biochemical assessment, hematoxylin and eosin (HE) staining and immunoblotting in the control and autophagy deficient mice. In vitro, RA protected RTECs against cisplatin-induced injury, activated autophagy and inhibited cisplatin-induced apoptosis. In vivo, RA attenuated cisplatin-induced tubular damage, shown by improved renal function, decreased renal cast formation, decreased NGAL expression and activated autophagy in the control mice. Furthermore, the nephrotoxicity of cisplatin was aggravated and the protective effect of RA was attenuated in autophagy deficient mice, indicating that RA works in an autophagy-dependent manner on CIAKI. RA activates autophagy and alleviates CIAKI in vivo and in vitro.Thus RA may be a renoprotective adjuvant for cisplatin-based chemotherapy.